Carpal tunnel syndrome (CTS) and exposure to vibration, repetitive wrist movements, and heavy manual work: a case-referent study. Issue 1 (January 1989) - Wieslander, G; Norbäck, D; Göthe, C J; Juhlin, L
Abstract : Possible connections between carpal tunnel syndrome (CTS) and exposure to vibrating handheld tools, repetitive wrist movements, and heavy manual work were examined in a case-referent study. The cases were 38 men operated on for CTS between 1974 and 1980. For each case, two referents were drawn from among other surgical cases (hospital referents) and two further referents from the population register and telephone directory, respectively (population referents). Thirty four of 38 cases (89%) and 143 of 152 referents (94%) were interviewed by telephone. An increased prevalence of obesity, rheumatoid disease, diabetes, or thyroid disease was observed among the cases but most did not suffer from any of these disorders. CTS was significantly correlated with exposure to vibration from handheld tools and to repetitive wrist movements but showed a weaker correlation with work producing a heavy load on the wrist. A cause-effect relation between CTS and exposures to handheld vibrating tools and to work causing repetitive movements of the wrist seems probable. Some differences between hospital and population referents indicate that a case-referent study of this type could be biased by inappropriate selection of referents.